A Novel Solution to the Problem of Old Evidence. Issue 3 (July 2015) - Sprenger, Jan
Abstract : One of the most troubling and persistent challenges for Bayesian Confirmation Theory is the Problem of Old Evidence (POE). The problem arises for anyone who models scientific reasoning by means of Bayesian Conditionalization. This article addresses the problem as follows: First, I clarify the nature and varieties of the POE and analyze various solution proposals in the literature. Second, I present a novel solution that combines previous attempts while making weaker and more plausible assumptions. Third and last, I summarize my findings and put them into the context of the general debate about POE and Bayesian reasoning.